Load characteristic of tractor three-point hitch for their simulation in laboratory condition - Š. Drabant; Z. Tkáč; M. Mojžiš (Research in Agricultural Engineering, 2006)
Presented paper is dealing with operation load of three-point hitch (TPH) of agriculture tractor in randomly changeable working conditions and their simulation in laboratory. The basic goal was to obtain experimental data, after which we can judge and analyze problematic of dynamic load of wheel tractor at plowing with orientation on TPH. Another goal was using obtained result from operating measures on their simulation in laboratory conditions by hydrostatic simulator. In presented paper is solved power analysis in each elements TPH of agricultural tractor ZTS 160 45URII A. The tractor during exploiting was in set with four-ploughshare carried and five-ploughshare semi-mounted plough. The measuring was realized for 3 varieties of set speed (gear ratio I/2, I/3, I/1), 3 depths of plowing (20, 25 and 27 cm) and 3 varieties of TPH - positional, mixed and draught control.